PENGERTIAN PENGUKURAN, EVALUASI DAN ASSESSMENT SERTA TUJUAN DAN FUNGSI EVALUASI DALAM PEMBELAJARAN PAI - Achmad Rasyid Ridha; Ahmad Akbar Al Faizi; Agus Sutrisno (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Measurement, evaluation, and assessment are essential components of the Islamic Religious Education (PAI) learning process because they play a role in assessing the achievement of overall educational goals. This study aims to examine the meaning of measurement, evaluation, and assessment and to explain the purpose and function of evaluation in Islamic Religious Education (PAI) learning. The research method used is library research, analyzing various sources, including books, scientific journals, and documents related to PAI learning evaluation. The results of the study indicate that measurement is the process of assigning scores to students' abilities, assessment is the systematic collection of information about the learning process and outcomes, and evaluation is the activity of making decisions based on the results of measurement and assessment. Evaluation in PAI learning aims to determine students' level of understanding, attitudes, and practice of Islamic values. It also serves as a feedback tool to improve the learning process, enhance the quality of learning, and assist teachers in determining follow-up actions. Therefore, a comprehensive understanding of the concepts of measurement, assessment, and evaluation is essential for the effective implementation of PAI learning evaluation and its alignment with the goals of Islamic education.